Sasakologi - Politeness Research in Sasak by Lalu Nurul Yaqin (International Journal of Linguistics and Indigenous Culture, 2023)
This is a book written by Lalu Nurul Yaqin to study about the communication dynamics of Sasak community in Lombok, Indonesia. The uniqueness of everyday conversation and discussions in Sasak’s wedding rituals has become a central part of this study. The objective of this book review article is to discuss the strengths and weaknesses of this book as well as giving recommendations. This book has analyse qualitative data that was recorded during the author’s field trips and attending rituals. However, the lack of visual images and thorough explanations has made it difficult to visualize the communication activities and rituals especially if the reader is not familiar with the traditions in Lombok. It was suggested that adding images and comparative studies from various sources regionally and internationally would greatly benefit the book. Overall, it is a comprehensive book suitable for students or academics in various fields such as anthropology, sociolinguistics, and communication.